Classification and diagnosis in orthopaedic trauma - Anwar, Rahij; Tuson, Kenneth W. R.; Khan, Shah Alam, F.R.C.S; Cambridge eBooks (Cambridge : Cambridge University Press, 2008)
A highly illustrated book providing concise yet comprehensive information on fracture classification and management. The text has been developed according to the requirements of orthopaedic surgeons in training. The first section covers general principles such as terminology and dealing with multiple trauma; following sections take the reader systematically through regions of the body and the various possible fractures, covering diagnosis, treatment and healing in each case. Definitive information on the ever-disputed issue of classification of musculoskeletal injuries is provided throughout. An effective reference book for the clinic, this book is also an indispensable tool for trainees in orthopaedic and emergency medicine and orthopaedic nurses.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Fractures -- Diagnosis; Fractures -- Treatment; Musculoskeletal system -- Wounds and injuries -- Diagnosis; Musculoskeletal system -- Wounds and injuries -- Treatment; Electronic books